Molecular composition modelling of petroleum fractions based on a hybrid structural unit and bond-electron matrix (SU-BEM) framework. (29th June 2019) - Feng, Song; Cui, Chen; Li, Kaiyu; Zhang, Linzhou; Shi, Quan; Zhao, Suoqi; Xu, Chunming
Highlights: A hybrid framework combining structural units and a bond-electron matrix is proposed. Flexibility of the probability density functions (PDFs) set-up module. Applicability of the method to different petroleum fractions from diesel to slurry oil. Abstract: In this paper, we developed a method to represent petroleum molecules and reconstruct the molecular composition of petroleum fractions. A hybrid framework combining structural units and a bond-electron matrix (SU-BEM) was proposed to represent petroleum molecules in a convenient way and retain all the detailed atomic information. The structural units and bond-electron matrix represent the basic structural components and the atom connectivity of petroleum molecules, respectively. The group contribution method was implemented in the framework to predict the physical and chemical properties of petroleum molecules based on their chemical structures. Good agreement was observed for the property calculations of pure low-carbon number components. A flexible probability density function (PDF) sequence module was developed and used in the sampling procedure to obtain the molecular quantities used in the compositional models. The PDF parameters, as well as molecular compositions, were optimized by minimizing the differences between predicted and experimental properties. The method was validated for applications involving diesel, vacuum gas oil, and fluid catalytic cracking slurry oil.